Behavioral Analysis of Caring Nurses In Hospital Inpatient Rooms: Systematic Literature Review - Putri Labibah Asrianto Sipayung; Zahroh Shaluhiyah; Luky Dwiantoro (Wacana Journal of Social and Humanity Studies, 2022)
Nursing services are based on the caring attitude of nurses who can improve the quality of nursing services. The caring behavior of nurses is provided through an approach where nurses work by increasing their concern for patients. But this is influenced by caring efficacy where a nurse is confident to express her concern for the patient. Previous research has explained that the prevalence of caring nurse behavior in some regions is indeed different. For this reason, further comparison and analysis are needed to be related to research on caring nurse behavior. A Literature search is carried out between 2017 and 2022 using the PubMed, Science Direct, Scopus, Google Scholar, and Proquest databases. The terms used in the search are factors, nurses caring behavior, inpatients, and hospitals. Inclusion and exclusion criteria are also applied in the search for related research articles. The percentage value of nurse-caring behavior has various categories, where the percentage of good nurse-caring behavior includes Indonesia, Ethiopia, the United States, Korea, Iran, and Singapore. Various studies have shown that many factors can influence nurse’s caring behavior, which can be classified into three main factors: 1) Individual Factors, including age, education, and length of service; 2) Psychological Factors, including co-worker relationships and job satisfaction; and 3) Organizational Factors, including supervision and workload. A systematic review of the three main factors influencing nurses’ caring behavior is expected to be a reference material in determining strategies for improving hospital HR skills, especially among nurses. Keywords: nurses, caring behavior, inpatients, hospital